2022
DOI: 10.1038/s41467-022-32286-0
|View full text |Cite
|
Sign up to set email alerts
|

Neolithic culinary traditions revealed by cereal, milk and meat lipids in pottery from Scottish crannogs

Abstract: Cereal cultivation in Britain dates back to ca. 4000 BCE, probably introduced by migrant farmers from continental Europe. Widespread evidence for livestock appears in the archaeozoological record, also reflected by ubiquitous dairy lipids in pottery organic residues. However, despite archaeobotanical evidence for domesticated plants (such as cereals), organic residue evidence has been near-absent. Our approach, targeting low-abundance cereal-specific markers, has now revealed evidence for cereals (indicating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…11,23,46 Previous studies have demonstrated that these distribution patterns are relatively stable and can be used for species identification in archaeological material, at least as old as the 4th millennium BCE. 10,12,36 If so, the pattern observed in this study suggests that a Triticum species was processed rather than barley, the other relevant cereal crop at the settlement. 27 This conclusion is based on the dominance of AR 21:0, a characteristic of wheat species, and the presence of AR 25:0, the predominant homologue in barley, in only one sample.…”
Section: Application To Archaeological Potterymentioning
confidence: 74%
See 4 more Smart Citations
“…11,23,46 Previous studies have demonstrated that these distribution patterns are relatively stable and can be used for species identification in archaeological material, at least as old as the 4th millennium BCE. 10,12,36 If so, the pattern observed in this study suggests that a Triticum species was processed rather than barley, the other relevant cereal crop at the settlement. 27 This conclusion is based on the dominance of AR 21:0, a characteristic of wheat species, and the presence of AR 25:0, the predominant homologue in barley, in only one sample.…”
Section: Application To Archaeological Potterymentioning
confidence: 74%
“…27 As discussed in Section 3.3.3, AR distribution patterns can be used for cereal species discrimination in modern samples. 10,[12][13][14]36 Its usage, however, has to be executed with care when dealing with archaeological samples because the AR homologues' concentration and distribution may change over time. 11,23,46 Previous studies have demonstrated that these distribution patterns are relatively stable and can be used for species identification in archaeological material, at least as old as the 4th millennium BCE.…”
Section: Application To Archaeological Potterymentioning
confidence: 99%
See 3 more Smart Citations